LANGUAGE STYLE IN INSTAGRAM COSMETIC ADVERTISEMENT - Nilawati Pangaribuan; Rezeki Laia; Gongsar Silaban (LPPM Universitas Darma Agung, 2020)
This article concerns with “Language style in Instagram cosmetic Advertisement such as; Make Over, Revlon, and Maybelline. The product from the five cosmetics Instagram is focused on facial beauty especially: eye shadow, lipstick, foundation, eyeliner, mascara. In completing the analysis, library research was applied, the result of the analysis was elaborated by using a quantitative method and conducted by applying Martin Joos' (2010). The data are analyzed to find out kinds of language style of advertisement, the dominant use of language style in advertisement and giving the reason of the most dominant type of language in Instagram cosmetic The result of the analysis proves that there are five kinds of language style in the advertisement such as; Frozen Style, Formal Style, Consultative Style, Casual Style,and Intimate Style.Consultative Style is the most dominant use of language style in the advertisements of Instagram